Electronically Coupled Heterojunctions Based on Graphene and Cu2−xS Nanocrystals: The Effect of the Surface Ligand - Ju Y. Shang; Mariangela Giancaspro; Adriana Grandolfo; Rafique A. Lakho; Elisabetta Fanizza; Suraj K. Patel; Giuseppe Valerio Bianco; Marinella Striccoli; Chiara Ingrosso; Oscar Vazquez-Mena; M. Lucia Curri (Molecules)
Optoelectronic devices combining single-layer graphene (SLG) and colloidal semiconducting nanocrystal (NC) heterojunctions have recently gained significant attention as efficient hybrid photodetectors. While most research has concentrated on systems using heavy metal-based semiconductor NCs, there is a need for further exploration of environmentally friendly nanomaterials, such as Cu2−xS. Chemical ligands play a crucial role in these hybrid photodetectors, as they enable charge transfer between the NCs and SLG. This study investigates the photoresponse of an SLG/Cu2−xS NCs heterojunction, comparing the effect of two short molecules—tetrabutylammonium iodide (TBAI) and 3,4-dimethylbenzenethiol (DMBT)—as surface ligands on the resulting structures. We have analysed charge transfer at the heterojunctions between SLG and the Cu2−xS NCs before and after modification with TBAI and DMBT using Raman spectroscopy and transconductance measurements under thermal equilibrium. The photoresponse of two hybrid devices based on three layers of Cu2₋xS NCs, deposited in one case on SLG/Cu2−xS/TBAI (“TBAI-only” device) and in the other on SLG/Cu2−xS/DMBT (“DMBT + TBAI” device), with a TBAI treatment applied, for both, after each layer deposition, has been evaluated under 450 nm laser diode illumination. The results indicate that the TBAI-only device exhibited a significant increase in photocurrent (4 μA), with high responsivity (40 mA/W) and fast response times (<1 s), while the DMBT + TBAI device had lower photocurrent (0.2 μA) and responsivity (2.4 μA), despite similar response speeds. The difference is attributed to DMBT’s π–π interactions with SLG, which enhances electronic coupling but reduces SLG’s mobility and responsivity.